Richard Rose y Caryn Peiffer, Paying Bribes for Public Services: A Global Guide to Grass-Roots Corruption, Nueva York, Palgrave Macmillan, 2015, 108 pp. - Rodríguez-Giménez, Vladimir (Gestión y Política Pública, 2021)
Reseña del libro Paying Bribes for Public Services: A Global Guide to Grass-Roots Corruption de Richard Rose y Caryn Peiffer.